Metastatic Osteosarcoma of Lacrimal Gland - Smitha K Shambhu; Saptagirish Rambhatla; Anup Chandak (Delhi Journal of Ophthalmology)
Osteosarcoma is the most common malignant tumor affecting the bone. Children and young adults are commonly affected. Metastasis from osteosarcoma mainly invoves the lungs and breast. Orbital metastasic disease is uncommon and lacrimal gland metastasis is even rarer. Here we report a case of lacrimal gland metastasis from osteosarcoma of the upper end of femur.